Sexual well-being after menopause: An International Menopause Society White Paper. (3rd September 2018) - Simon, J. A.; Davis, S. R.; Althof, S. E.; Chedraui, P.; Clayton, A. H.; Kingsberg, S. A.; Nappi, R. E.; Parish, S. J.; Wolfman, W.
Abstract: Sexual well-being frequently declines following the menopause transition and can be associated with significant personal and relationship distress. This distress is the hallmark of female sexual dysfunction (FSD). FSD is highly prevalent in postmenopausal women. The prevalence of sexual problems increases with age, but conversely this is associated with decreasing distress with advancing age. This pattern has been seen across multiple international populations with varied cultural norms. While the etiology of FSD is multifactorial, the physiological changes of sex hormone insufficiency and postmenopausal symptoms, such as dyspareunia, are primary factors contributing to FSD at midlife. The International Menopause Society is working to increase awareness of FSD and to provide a framework for practitioners to address sexual medicine concerns. This White Paper aims to review the process of care for female sexual well-being following menopause, from initially approaching the discussion of FSD, to identifying clinical signs and symptoms, and ultimately determining the best available biopsychosocial therapies. As with most processes of care, the first step is often the most difficult. Health-care practitioners need to broach the topic of sexuality in the clinical setting. Lack of information on, comfort with, and biases about the topic of sexuality after menopause are significant hurdles that the International Menopause Society addresses in this document. Each member of the Writing Group remains committed to continued advocacy for the validity of FSD as a diagnosis, the need for therapies for women to be both available and included in health insurance coverage, and continued therapeutic research to provide evidence-based solutions.